Potential Of Indonesian Millennial Cash Waqf And Innovation - Hoessien, Jalaluddin; Insani, Muhammad Fitrah; Juzaili, Khair (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Cash waqf is one of the potential financial instruments in supporting social and economic development in Indonesia. The millennial generation, with its strong connection to digital technology, has great potential to increase participation in cash waqf through digital innovation. This study aims to analyze the potential of cash waqf among the millennial generation in Indonesia and identify innovations that can enhance such participation. Through a descriptive approach and qualitative analysis of relevant literature, this study finds that technological innovations, such as digital platforms and mobile applications, can expand the reach and transparency of cash waqf management. The estimated potential of cash waqf from millennial participation ranges from IDR 684 billion to IDR 2.052 trillion per year, depending on the level of participation. The results of this study indicate that with the right approach, cash waqf can become a significant instrument to support sustainable development in Indonesia.